Breast Reconstruction Practices and Barriers in West Africa: A Survey of Surgeons. Issue 11 (November 2020) - Ranganathan, Kavitha; Ogunleye, Adeyemi A.; Aliu, Oluseyi; Agbenorku, Pius; Momoh, Adeyiza O.
Abstract : Background: Access to breast reconstruction is limited in low-income countries. Identifying current barriers that plague both providers and patients can inform future interventions focused on improving access to care. The goal of this study was to delineate perceptions of breast reconstruction among providers in West Africa and define current barriers to care. Methods: Surveys were administered to surgeons attending the annual meeting of the West African College of Surgeons in 2018. Surgeons were surveyed regarding their practices and perceptions of breast reconstruction. Information on barriers to breast reconstruction focused on patient- and surgeon-related factors was also obtained. A univariate analysis was performed to assess association of demographic and practice information with perceptions of reconstruction barriers. Results: Thirty-eight surgeons completed the questionnaires; 10 of the respondents were plastic surgeons (27%). The survey response rate was 40%. Factors that a majority of surgeons believed to limit access to reconstruction included limited experience (72.9%), resources (76.3%), and a lack of referrals for reconstruction (75%). In total, 76.5% of surgeons had performed <10 breast reconstruction cases in the past year. Two patient factors highlighted by most surgeons (>80%) were a lack of knowledge and concerns about cost. Conclusions: Perspectives from surgeons in the West African College of Surgeons suggest that barriers in access, patient awareness, surgeon technical expertise, and cost limit the delivery of breast reconstructive services to women in the region. Implementation of interventions focused on these specific metrics may serve as valuable first steps in the movement to increase access to breast reconstruction.